PENGARUH KEPEMIMPINAN ETIS TERHADAP PRESTASI KERJA PEGAWAI (STUDI KASUS PADA KANTOR PAJAK PRATAMA TOBELO KABUPATEN HALMAHERA UTARA) - DjelaDjela, Kristian Soleman; Pio, Riane Johnly; Sambul, Sofia A. P. (Sam Ratulangi University, 2017)
This study aims to determine whether the influence of ethical leadership on the performance of employees at the Tax Office Primary Tobelo Halmahera Utara. In this study using descriptive quantitative is to test the relationship between variables and to measure the magnitude of influence on these variables. Based on this research shows that ethical leadership has a positive and very strong influence on employee performance, thus hypothesis states there is influence of ethical leadership on employee performance can be accepted. A leader with an ethical leadership style can influence individuals or groups to behave in accordance with organizational or corporate goals. Therefore companies or organizations need to pay attention to matters that include ethical behavior so that employee performance can be developed for the progress of the organization or companyKeywords: Ethical Leadership, Work Achievement.